2011
DOI: 10.3945/ajcn.111.018762
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-linolenic acid, linoleic acid, and n–3 long-chain PUFA and risk of ischemic heart disease

Abstract: This study suggests that there is no association between ALA intake and risk of IHD, but a high intake of n-3 LC-PUFA had a significant cardioprotective effect in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 34 publications
0
30
1
Order By: Relevance
“…After screening the titles and abstracts, 566 full-text articles were evaluated which 6 original articles were identified as being appropriate for inclusion in this meta-analysis. 2429 We also obtained permission from principal investigators of the cohort studies presented in the Pooling Project of Cohort Studies on Diet and Coronary Disease, 4 to examine the association between LA intake and CHD risk and included these results in the meta-analysis. The characteristics of these cohort studies in the pooling project were described elsewhere in detail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the titles and abstracts, 566 full-text articles were evaluated which 6 original articles were identified as being appropriate for inclusion in this meta-analysis. 2429 We also obtained permission from principal investigators of the cohort studies presented in the Pooling Project of Cohort Studies on Diet and Coronary Disease, 4 to examine the association between LA intake and CHD risk and included these results in the meta-analysis. The characteristics of these cohort studies in the pooling project were described elsewhere in detail.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we included the results of three other previously published studies. 24,25,29 In the NHS and HPFS, we updated the published analyses with longer follow-up: from 20 years in previous publications to 30 years in the NHS, and from 6 years to 24 years in the HPFS. In addition, we reanalyzed data in ATBC study to adjust for the confounding variables similar to other included cohort studies in this meta-analysis (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In older epidemiological studies, Oomen et al and Simon et al found no association between ALA intake and CHD risk [216,217]. More recently, Vedtofte et al suggested that there is no association between ALA intake and risk of ischemic heart disease [218] and Lemtaire et al concluded that ALA is not associated with incident congestive heart failure (CHF) in older adults [219], which is in agreement with findings from another prospective study by Gode et al reporting no association between ALA intake and incident CHD [220].…”
Section: 1 Epidemiological Associationsmentioning
confidence: 98%
“…Besides, the additive effect of α-linolenic acid (ALA) and n-3 long-chain PUFA was observed to exhibit cardio-protective effects in women [11], which led to consequent human clinical studies of chia on disease risk factors. To date, four clinical trials have been carried out.…”
Section: Introductionmentioning
confidence: 99%